Integration of Green Economy, Biochar-Agroecology, and GreenSCOR for Sustainable Food and Feed Security in Karang Taruna Gempur Samarinda - Ida Rosanti; Purbawati; Sri Endayani (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This program integrates the Green Economy model, Biochar Agroecology, and the GreenSCOR framework to strengthen sustainable food and feed security in Karang Taruna Gempur Samarinda. The activity aims to improve youth capacity in managing local resources through the application of biochar from biomass waste, agroecological practices, and environmentally oriented supply chain management. Implementation methods included socialization, technical training, and participatory mentoring. The results show a 35% increase in production efficiency, a 40% reduction in organic waste, and improvements in water quality and fish productivity. In addition, a youth led green economic enterprise was formed to enhance local economic independence. These findings indicate that the integration of technological innovation and community empowerment effectively supports sustainable food and feed security while promoting an inclusive green economy at the community level.